Formulasi Gel dan Karakterisasi Mutu Fisik Ekstrak Etanol Daun Dadap Serep (Erythrina subumbrans) dengan Variasi Gelling Agent HPMC dan Carbopol - Danang Raharjo; Ones Kotouki; Anna Fitriawati (Pusat Riset dan Inovasi Nasional, 2026)
Dadap serep leaves (Erythrina subumbrans) contain flavonoid compounds with antioxidant and anti-inflammatory activities, thus have potential to be developed as topical gel preparations. This study aimed to formulate and characterize the physical quality of ethanol extract gel of dadap serep leaves with variations of HPMC and Carbopol 940 as gelling agents and to determine the best formula. The extract was obtained by maceration method using 96% ethanol. Gels were prepared in five formulas with variations in HPMC and Carbopol 940 concentrations: F I (HPMC 2%), F II (Carbopol 0.5% + HPMC 1.5%), F III (Carbopol 2%), F IV (Carbopol 1% + HPMC 1%), and F V (Carbopol 1.5% + HPMC 0.5%). Physical quality evaluation included organoleptic, homogeneity, pH, viscosity, spreadability, and adhesion tests. Data were analyzed using one-way ANOVA followed by Tukey's post-hoc test (α=0.05). The results showed that variations in gelling agents significantly affected pH (p<0.05), viscosity (p<0.001), spreadability (p<0.05), and adhesion (p<0.001). The higher the Carbopol concentration, the viscosity and adhesion increased but spreadability decreased. All formulas had brownish-green color, characteristic extract odor, thick consistency, good homogeneity, and pH within the range of 4.5-6.5. Formula I had adhesion of 3.1 seconds which did not meet the requirement (>4 seconds). Formula II (Carbopol 0.5% + HPMC 1.5%) was selected as the best formula because it met all requirements with pH 5.62, viscosity 12,670 cPs, spreadability 6.2 cm, and adhesion 4.2 seconds, showing an optimal balance between ease of spreading and adhesive ability. Further research is recommended including long-term stability tests, pharmacological activity tests, and safety tests of the preparation.